2009
DOI: 10.1586/14737159.9.2.165
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ release assays in tuberculosis management in selected high-risk populations

Abstract: Tuberculosis (TB) is the most deadly infectious disease in the world. TB control relies on passive case findings and targeted treatment of latently infected individuals at high risk of disease progression. Tuberculin skin testing (TST) is conventionally used for detection of TB infection. Recently, blood assays measuring the release of IFN-gamma by TB-specific effector memory T cells have been developed to overcome TST limitations. Overall, IFN-gamma release assays are more specific than TST, more sensitive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…The performance of IGRAs is impaired for HIV-infected patients with advanced immunodeficiency. Higher rates of indeterminate results are found for patients with CD4 counts below 100 cells/l, due to low levels of IFN-␥ in response to stimulation with the positive control (24).…”
Section: Ifn-␥ Release Assays For Hiv-infected Patientsmentioning
confidence: 95%
See 1 more Smart Citation
“…The performance of IGRAs is impaired for HIV-infected patients with advanced immunodeficiency. Higher rates of indeterminate results are found for patients with CD4 counts below 100 cells/l, due to low levels of IFN-␥ in response to stimulation with the positive control (24).…”
Section: Ifn-␥ Release Assays For Hiv-infected Patientsmentioning
confidence: 95%
“…These assays detect the release of the cytokine gamma interferon (IFN-␥) from T lymphocytes after stimulation with the M. tuberculosis-specific antigens early secretory antigen target 6 (ESAT-6) and culture filtrate protein 10 (CFP-10) and also TB antigen TB 7.7 for the QFT-GIT test (24,74). The QuantiFERON assays use anticoagulated whole blood and measure the release of gamma interferon into the supernatant by enzyme-linked immunosorbent assays (ELISAs), while the T-SPOT.TB assay uses isolated blood mononuclear cells and determines the number of gamma interferon-secreting cells in the sample by using an enzymelinked immunospot (ELISPOT) technique (24,74). Each test is performed with a negative control and a positive control, and results are reported as being indeterminate if there is a high signal for the negative control or a low signal for the positive control.…”
Section: Ifn-␥ Release Assays For Hiv-infected Patientsmentioning
confidence: 99%
“…39 However some studies have shown that IGRAs (particularly the TBSPOT.TB assay) might be more sensitive than the TST in detecting latent TB infection in people who are HIV infected with severe immune suppression. [40][41][42][43][44][45][46][47] A study in South Africa demonstrated that patients with very low CD4 counts who had recently been treated for active TB had high rates of response using the TSPOT.TB test. This study suggested that the TSPOT.TB has utility even in a population that had a mean CD4 + T-cell count of 98.…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have shown the accuracy of the TB IGRA (14)(15)(16)(17). These assays are now used in a number of countries worldwide (17)(18)(19).…”
Section: Advantagesmentioning
confidence: 99%
“…The use of these specific proteins results in improved specificity compared to the use of TST to detect active TB disease. Additionally, studies show the use of IGRAs in screening for active tuberculosis is cost-effective, especially when screening high-risk populations, such as immigrants, close contacts of individuals with active tuberculosis, and health care workers (12,14,(20)(21)(22)(23).…”
Section: Advantagesmentioning
confidence: 99%